2021
DOI: 10.3390/su132011521
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Workforce Sustainability, Stress, and Career Decision: A Study of Kindergarten Teachers during the COVID-19 Pandemic

Abstract: A shortage of qualified teachers has been a long-term problem in many school districts and education systems internationally. During the COVID-19 pandemic, the current human resource gap in teaching significantly impacted the quality of teaching services and the experience of all school parties. Based on social cognitive career and motivation theory, two research questions guided this study: (1) Why did kindergarten teachers decide to leave their teaching positions and education professions permanently during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Similarly, some studies showed that long-term screen use causes health problems (Nagata et al, 2020 ; Wong et al, 2021 ). Furthermore, it has been determined that exposure to intensive technology use triggers technology addiction (Colomo Magaña et al, 2021 ), stress, burnout and technology-related concerns during the COVID-19 process are effective on teachers’ career and retirement preferences (Dos Santos, 2021 ). According to the results of the study, it was detected that the teachers neglected their loved ones due to the long-distance education processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similarly, some studies showed that long-term screen use causes health problems (Nagata et al, 2020 ; Wong et al, 2021 ). Furthermore, it has been determined that exposure to intensive technology use triggers technology addiction (Colomo Magaña et al, 2021 ), stress, burnout and technology-related concerns during the COVID-19 process are effective on teachers’ career and retirement preferences (Dos Santos, 2021 ). According to the results of the study, it was detected that the teachers neglected their loved ones due to the long-distance education processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, it was not enough to acquire numerous ICT; teachers had to face the stress of teaching in a scenario they had never experienced before [ 14 , 15 ]. Many of them at many different educational levels were unable to cope with the situation of increased stress and isolation [ 16 ], even abandoning their professional careers [ 17 ]. Other teachers coped with the situation by applying active and effective learning strategies in order to reduce the risk of increasing their stress and burnout [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout chases away over 50% of U.S.A. clerics in their first five years of work [ 24 ], kindergarten teachers leading them to new careers in Spain [ 25 ], and almost 50% of Romania’s trained clerics who choose to reconvert professionally or not to work at all.…”
Section: Introductionmentioning
confidence: 99%